Organochlorine Pesticides in Three Fish Samples (Dhaka University Journal of Science, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/dujs.v61i2.17075 Dhaka Univ. J. Sci. 61(2): 215-216, 2013 (July)